The effect of social grooming via live photo-sharing on well-being: the mediating role of social capital and moderating role of the need for privacy - Fei Wang; Xin Wang (Frontiers in Psychology, 2025)
BackgroundDigital citizens in the social media era can share various types of photos. Live photo features on closed platforms, such as WeChat Moments, offer users a vivid sense of presence. However, the spontaneous nature of live photos may unintentionally reveal audio or visual details, raising privacy concerns. Previous research has not fully explored why users share live photos despite these risks, nor how live photo sharing affects users’ well-being from a social grooming perspective.MethodsWe surveyed 266 users of WeChat Moments and analyzed the data using a moderated mediation model. Social capital was tested as a mediator between live photo-based social grooming and well-being, with the need for privacy as a moderator.ResultsSocial grooming through live photo sharing was positively associated with users’ well-being, and this association was mediated by social capital. Additionally, the strength of this positive association varied depending on users’ need for privacy. Specifically, a higher need for privacy was associated with a weaker relationship between social grooming and well-being, indicating that privacy concerns might constrain the potential benefits of social grooming.ConclusionSocial grooming via live photo sharing is associated with enhanced well-being through social capital, but the strength of this association depends on users’ need for privacy. To better balance social grooming and privacy protection, platforms and users should consider adopting flexible, user-controlled visibility settings.